Perlunya Perubahan Paradigma Dari New Public Management ke New Public Governance di Indonesia - Muchamad Zaenuri (Universitas Islam Indonesia, 2012)
Innovation in the process and services of local government should be dynamic and firmly based on a clear conceptual foundation guaranteed by law. In will be not a long time to wait till the local governments may enjoy certain degree of freedom to initiate an innovation, since the draft or the bill on Local Governement grants such opportunity. Considering that innivation in the process and services of the government facing many barriers, it is needed therefore, not merely legal bases, but also the conceptual basis (paradigm) must be well formulated. The paradigm new public governance (NPG) which offers a concept ofinnivation based on the collaboration of three pillars of governance; goverment, private entities and society, seems to be prospective for being the basis of such innovation.Key words : innovation, governance, local government